Prognostic and predictive role of gene mutations in chronic lymphocytic leukemia: results from the pivotal phase III study COMPLEMENT1 - Tausch, Eugen; Beck, Philipp; Schlenk, Richard Friedrich; Jebaraj, Billy J.; Dolnik, Anna; Yosifov, Deyan Y.; Hillmen, Peter; Offner, Fritz; Janssens, Ann; Babu, K. Govind; Grosicki, Sebastian; Mayer, Jiri; et al. (Haematologica, 2020)
Next generation sequencing studies in Chronic lymphocytic leukemia (CLL) have revealed novel genetic variants that have been associated with disease characteristics and outcome. The aim of this study was to evaluate the prognostic value of recurrent molecular abnormalities in patients with CLL. Therefore, we assessed their incidences and associations with other clinical and genetic markers in the prospective multicenter COMPLEMENT1 trial (treatment naive patients not eligible for intensive treatment randomized to chlorambucil (CHL) vs. ofatumumab-CHL (O-CHL)). Baseline samples were available from 383 patients (85.6%) representative of the total trial cohort. Mutations were analyzed by amplicon-based targeted next generation sequencing (tNGS). In 52.2% of patients we found at least one mutation and the incidence was highest in NOTCH1 (17.0%), followed by SF3B1 (14.1%), ATM (11.7%), TP53 (10.2%), POT1 (7.0%), RPS15 (4.4%), FBXW7 (3.4%), MYD88 (2.6%) and BIRC3 (2.3%). While most mutations lacked prognostic significance, TP53 (HR2.02,p<0.01), SF3B1 (HR1.66,p=0.01) and NOTCH1 (HR1.39,p=0.03) were associated with inferior PFS in univariate analysis. Multivariate analysis confirmed the independent prognostic role of TP53 for PFS (HR1.71,p=0.04) and OS (HR2.78,p=0.02) and of SF3B1 for PFS only (HR1.52,p=0.02). Notably, NOTCH1 mutation status separates patients with a strong and a weak benefit from ofatumumab addition to CHL (NOTCH1wt:HR0.50,p<0.01, NOTCH1mut:HR0.81,p=0.45). In summary, TP53 and SF3B1 were confirmed as independent prognostic and NOTCH1 as a predictive factor for reduced ofatumumab efficacy in a randomized chemo (immune)therapy CLL trial. These results validate NGS-based mutation analysis in a multicenter trial and provide a basis for expanding molecular testing in the prognostic workup of patients with CLL. ClinicalTrials.gov registration number: NCT00748189
Gesehen am 13.11.2020